Menghadapi Dunia Teknologi Modern: Peluang, Ancaman Dan Perlindungan Digital Sebagai Pencegahan SDGs 1 - Verra Rosyalia Widia Sofyan; Ilman Aldi Nurrohman; Putri Fajri Maulida (Journal of Empowerment Community, 2026)
Community service on dealing with modern technology is one form of providing understanding and empowerment to the community in efforts to reduce and overcome poverty issues. In addition, this is also a manifestation of the implementation of the 17 Sustainable Development Goals (SDGs) targeted to be achieved by 2030. The implementation of this community service is carried out through an extension approach by holding seminars and providing sample financial reports for business actors so they can separate personal finances and business finances. The results of the implementation of the community service activities showed a positive response and high enthusiasm from the community who participated in the extension activities. This was evident in their attention and sincerity when following the explanations given, taking notes on important things conveyed and business actors who brought product samples as proof of business actors.